Religious Meaning and Social Motivation in the Practice of Infaq and Sadaqah: A Qualitative Study of Rural Muslim Communities in Suoh Village, West Lampung, Indonesia - Nuraeni Nuraeni; Putri Vika Nurwinda (Journal of Contemporary Applied Islamic Philanthropy, 2025)
Purpose: This study aims to explore the religious meaning and social motivation underlying the practice of sedekah among rural communities in Suoh Village, Liwa, West Lampung, with a particular focus on the subjective interpretations of community members regarding charitable giving. Methodology: This research employed a qualitative approach using purposive sampling to select key informants who routinely practiced sedekah. Data were collected through in-depth interviews and analyzed using an interpretive qualitative framework. Findings: The findings reveal that sedekah is perceived as: (1) an act of worship to strengthen spiritual closeness to God, (2) a means of purifying wealth and the heart, and (3) an expression of social solidarity within the community. The primary motivations include religious faith, expectations of spiritual rewards, and empathy toward others. The main challenges identified involve limited transparency in fund management and insufficient public understanding of distinctions among Islamic charitable instruments. The novelty of this study lies in its emphasis on the subjective religious meanings and social motivations of rural community members in practicing sedekah, highlighting the role of local values and lived religious experiences in shaping philanthropic behavior. The study recommends the digitalization of financial record-keeping and the development of community-based economic empowerment programs funded through sedekah to enhance social and economic impact.